18F-FDG PET/CT in a Case of Metastatic Breast Cancer to the Vulva. (July 2019) - Guglielmo, Priscilla; Paderno, Mariachiara; Elisei, Federica; Guerra, Luca; Landoni, Claudio; Buda, Alessandro; Crivellaro, Cinzia
Abstract : Abstract: A 56-year-old woman, previously treated for breast cancer, presented to gynecologists with a lump of the left labium major of the vulva. The FDG pattern resembled as a cIV stage vulvar cancer, whereas biopsy indicated metastases from breast cancer. Metastatic disease to the vulva is particularly uncommon, representing 5% to 8% of all vulvar cancer lesions. However, gynecological uptakes, including vulvar site, have to be kept in mind as a possible site of metastatic lesions from breast cancer.